Exploring Customer Interest in Faedah IB Savings: A Comprehensive Analysis - Qurrotu Aini; Mohamad Toha; Sundari; Freddrick Tiagita Putra (Create: Journal of Islamic Management and Business, 2025)
Marketing efforts play a crucial role in attracting customers to use BRI Syariah’s products, aiming to make these products easy to sell and widely appealing to both existing and potential customers. This study aims to explore customer interest in the Faedah iB savings product at Bank BRI Syariah KCP Mojosari, Mojokerto. To address this objective, a descriptive qualitative approach with a case study method was employed. The data analysis reveals several key findings: 1) Attention, Customers are aware of the Faedah iB savings product primarily through their own initiative in visiting the bank and receiving direct information from BRI Syariah staff. 2) Interest Customers are drawn to the Faedah iB savings due to its alignment with their individual background and the high-quality service provided by BRI Syariah during the process. Customers feel well served and receive clear explanations regarding the product’s details. 3) Desire Customers’ interest in the costs associated with the Faedah iB savings product depends on their personal perspectives and financial capabilities. Many opt for products with lower costs that can serve as a means of saving money for their internal needs. 4) Action Customers are motivated to use the Faedah iB savings account to support their business needs. 5) Halal Lifestyle Awareness Customers also aim to meet financial needs while shifting their perspective towards selecting products that align with their values, particularly in terms of a halal lifestyle.